SOME COMMENTS ON THE LATIN NAMING OF CHEMICAL TERMS, OXIDES AND ACIDS IN MEDICINE (Journal of Universal Science Research, 2024)
This is the abstract of Chemical terminology, names of chemical elements acids and oxides. In this article, I have mentioned about the chemical terminologies of the elements some of the important acids and oxides. I have also mentioned about the uses of these substance in our body how they help in various metabolic activities etc.